The amyloid precursor protein (APP) binds the PIKfyve complex and modulates its function. (9th February 2016) - Currinn, Heather; Wassmer, Thomas
Abstract : Phosphoinositides are important components of eukaryotic membranes that are required for multiple forms of membrane dynamics. Phosphoinositides are involved in defining membrane identity, mediate cell signalling and control membrane trafficking events. Due to their pivotal role in membrane dynamics, phosphoinositide de-regulation contributes to various human diseases. In this review, we will focus on the newly emerging regulation of the PIKfyve complex, a phosphoinositide kinase that converts the endosomal phosphatidylinositol-3-phosphate [PI(3) P ] to phosphatidylinositol-3, 5-bisphosphate [PI(3, 5) P 2 )], a low abundance phosphoinositide of outstanding importance for neuronal integrity and function. Loss of PIKfyve function is well known to result in neurodegeneration in both mouse models and human patients. Our recent work has surprisingly identified the amyloid precursor protein (APP), the central molecule in Alzheimer's disease aetiology, as a novel interaction partner of a subunit of the PIKfyve complex, Vac14. Furthermore, it has been shown that APP modulates PIKfyve function and PI(3, 5) P 2 dynamics, suggesting that the APP gene family functions as regulator of PI(3, 5) P 2 metabolism. The recent advances discussed in this review suggest a novel, unexpected, β-amyloid-independent mechanism for neurodegeneration in Alzheimer's disease.